Drosophila chaoptin, a member of the leucine-rich repeat family, is a photoreceptor cell-specific adhesion molecule. - Krantz, D.E.; Zipursky, S.L. (The EMBO Journal, 1990)
Drosophila chaoptin, required for photoreceptor cell morphogenesis, is a member of the leucine-rich repeat family of proteins. On the basis of biochemical and genetic analyses we previously proposed that chaoptin might function as a cell adhesion molecule. To test this hypothesis, chaoptin cDNA driven by the hsp 70 promoter was transfected into non-self-adherent Drosophila Schneider line 2 (S2) cells. Following heat shock induction of chaoptin expression, the transfected S2 cells formed multicellular aggregates. Mixing experiments of chaoptin expressing and non-expressing cells suggest that chaoptin expressing cells adhere homotypically. Previously it was shown that chaoptin is exclusively localized to photoreceptor cells. Thus, chaoptin is a cell-type-specific adhesion molecule. Biochemical analyses presented in this paper demonstrate that chaoptin is linked to the extracellular surface of the plasma membrane by covalent attachment to glycosyl-phosphatidylinositol. We propose that chaoptin and several other members of the leucine-rich repeat family of proteins define a new class of cell adhesion molecules.